Burden and inequalities of chronic kidney disease attributable to diet globally, regionally and temporally, 1990–2021 - Wei, Nana; Yang, Miao; Zheng, Pingping; Xu, Jian (Frontiers in Nutrition, 2025)
BackgroundModifiable dietary habits are a crucial means of reducing the risk of CKD. However, there is currently a lack of global-scale analysis on the burden of CKD attributable to diet. This study aimed to examine the burden of CKD potentially associated to diet globally, regionally and temporally.MethodOur research utilized data sourced from the 2021 edition of the Global Burden of Disease (GBD) study. We gathered information on the worldwide impact of diet-related CKD spanning from 1990 to 2021, categorizing this impact based on various factors including gender, age, GBD geographical regions, and individual countries. To assess the evolving trend of diet-attributable CKD burden over this period, we employed the Joinpoint regression model, calculating the average annual percent change (AAPC) for a comprehensive understanding. Cluster analysis was employed to classify countries into distinct dietary risk categories.ResultsIn 2021, globally, CKD burden potentially associated to diet resulted in 317,010 deaths (95% UI: 185,370–454,850) and 7,971,280 DALYs lost (95%UI: 4,630,030–11,451,430). These figures accounted for 20.75% of all CKD-related deaths and 17.93% of all CKD-related DALYs. The age-standardized mortality and DALY rates potentially associated to diet rose notably, reaching 3.83 (95%UI: 2.25–5.49) and 93.52 (95%UI: 54.29–134.38) per 100,000 population, respectively. However, significant regional variations were observed in these rates, with Central Sub-Saharan Africa experiencing the highest and Eastern Europe the lowest. High-income North America experienced a particularly steep increase, with an AAPC of 2.93% (95% CI: 2.85, 3.01%) for deaths and 2.51% (95%CI: 2.44, 2.56%) for DALYs. Among dietary factors, insufficient intake of fruits and vegetables emerged as the primary contributor to the CKD burden. By cluster analysis, seven clusters of dietary risk patterns were identified.ConclusionDiet may play a substantial role in the burden of CKD, with notable variations across different regions. It is imperative to implement enhanced dietary guidelines, with particular attention to mitigating the challenges faced by low-income countries and reversing the upward trend in high-income countries.